IMPLEMENTATION OF THE GUIDED INQUIRY MODEL LEARNING TO REDUCE MISCONCEPTIONS OF STATIC FLUID MATERIALS STUDENTS OF STATE JUNIOR HIGH SCHOOL 19 SAMARINDA SEMESTER II, 2019/2020 ACADEMIC YEAR - Helda Verawahyuni (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2022)
This classroom action research (CAR) aimed to describe teacher performance in implementing laboratory-based guided inquiry with the main target of reducing the number of students' misconceptions about static fluid material. Three indicators of the success of the action, namely: (1) the implementation and quality of static fluid learning using guided inquiry, (2) changes in student activity and motivation shown from cycle to the next cycle, and (3) a decrease in the number of target students experiencing fluid misconceptions (MK). Implementation, learning quality, and student activity were collected using observation and documentation techniques. The number of MK students was determined based on the results of the conception test on static fluid material before and after the action. CAR was conducted at SMP Negeri 19 Samarinda with the source of teacher observations, the learning process in class, and students of class VIII-A. The data were analyzed descriptively. Reflection and evaluation of data is the final step in the action research process. The results of this CAR show that the three indicators for the success of the action have been achieved. Static fluid learning using laboratory-based guided inquiry can be carried out with very good qualifications. Increased activity and motivation showed by students during the learning process from cycle to cycle. The number of target students who experience liquid fluid misconceptions has decreased from cycle to cycle.